Ответы и объяснения

Лучший Ответ!
2013-10-19T16:58:35+00:00
(х^2+2x-(11x-2)/3х+1):(х+1-(2х^2+х+2)/3х+1)=(3х^3+3x^2+6x^2+2x-11x-2)/3x+1 : (3x^2+x+3x+1-2x^2+x+2)/3х+1=(3x^3+3x^2+6^2+2x-11x-2)*(3x+1)
----------------------------------------------------------------------------------------------------  =
(3x+1)*(3x^2+x+3x+1-2x^2+x+2)

= 6x^2-3x-2
-------------------  =
-2x^2+2x+3
= вынесем минус и получится   (-6x^2+3x+2)*1
                                               ---------------------- = минус разделить на минус =
                                                 (-2x^2+2x+3)*1
 плюс, значит равно = (6x^2+3x+2)*1
                                 ----------------------  = 3
                                 (2x^2+2x+3)*1
Я думаю так...